Do Liver Transplant Recipients Have a Higher Risk for Cryptococcosis Than Non-liver Transplant Recipients?. (4th October 2017) - Sun, Hsin-Yun; Cheng, Aristine; Ho, Cheng-Maw; Hu, Rey-Heng; Chou, Nai-Kuan; Wang, Shoei-Shen; Chen, Yee-Chun; Chang, Shan-Chwen
Abstract: Background: Patients with liver cirrhosis have an increased risk for cryptococcosis. However, it is unknown whether they remain at a higher risk for cryptococcosis after liver transplantation. Methods: Patients undergoing solid organ transplantation at a tertiary hospital in Taiwan were included for analysis. Cryptococcosis was defined based on criteria proposed by the European Organization for Research and Treatment in Cancer and the Mycoses Study Group. Only Nystatin oral suspension but no systemic anti-fungal agents was prescribed routinely post-transplant. Results: From 2001 to 2016, in total, 1576 patients underwent solid organ transplantation, including 756 kidney, 411 liver, 336 heart, 61 lung, and 12 multi-organ transplantation. Cryptococcosis developed in 20 patients (1.3%), including cryptococcemia in 9, pulmonary/urine in 6, meningitis in 3, and surgical site infection in 2. Its incidence was 3.2% (13/411) in liver, 1.5% (5/336) in heart, and 0.3% (2/756) in kidney transplant recipients. Compared with 1165 non-liver transplant recipients, 441 liver transplant recipients had a significant higher incidence of cryptococcosis (3.1% vs. 0.6%, P < 0.01) and developed the disease with a shorter median duration after transplantation (75 vs. 213 days). Cryptococcosis with very-early onset (<30 days after transplantation) developed in 38.5% (5/13) of liver transplant recipients with cryptococcosis, but only 14.3% (1/7) in non-liver transplant recipients. Six patients (30%) died after a median follow-up duration of 399 days, and only two deaths were related to cryptococcosis. Conclusion: Our findings showed that liver transplant recipients still had a higher risk for cryptococcosis, and the disease developed earlier after transplantation than non-liver transplant recipients. Disclosures: All authors: No reported disclosures.